KEPEMILIKAN TANAH SECARA GUNTAI (ABSENTEE) DI KECAMATAN GUNUNG TOAR BERDASARKAN PERATURAN PEMERINTAH NOMOR 224 TAHUN 1961 JO PERATURANPEMERINTAH NOMOR 41 TAHUN 1964 TENTANG PELAKSANAAN PEMBAGIAN TANAH DAN PEMBERIAN GANTI KERUGIAN - Rahmat Septiadi; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Land has an important role for human life because human life cannot be separated from land.In the regulations that have been set forth in Article 10 paragraph 1 of Law number 5 of 1960concerning Basic Agrarian Regulations it stipulates that: